Performance evaluation of multimedia communications systems supported by IEEE 802.6 DQDB MAN. - Vallée, Richard. (University of Ottawa (Canada), 1990)
The work of this thesis is concerned about the performance evaluation of multimedia communications systems supported by IEEE 802.6 DQDB MAN (Distributed Queue Dual Buses Metropolitan Area Network). The proposed IEEE 802.6 DQDB MAN standard, more commonly called DQDB, defines a high speed network allowing integration of voice and data over circuit and packet switching networks. Such networks may be particularly useful for multimedia applications within medical environments involving the transfer of voice and high resolution images. Another application of DQDB can be a backbone network interconnecting low-speed LANs (local area networks). Simulation results, based on the development of queueing models by using the QNAP2 (Queue Network Analysis Package) simulation software, show that DQDB performs well in the above mentioned applications. However, since DQDB transfers information over short fixed-length slots, congestion problems related to the slot formatting process are observed under certain system configurations for multimedia applications. In order to reduce these congestion problems, two system improvements are proposed. The first is to consider the use of images compressed according to the technique called the reduced-difference pyramid while the second one is to allocate higher access priority to the gateways in the LANs interconnected by DQDB.
Keywords: Engineering, Electronics and Electrical.